PATIENT SATISFACTION – A VITAL TOOL OF HEALTHCARE EFFECTIVENESS: A PREFERENTIAL STUDY AT TIRUNELVELI DISTRICT - Sundari, M.Shunmuga; Sathic, A.jafar; A.Seetharaman (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Patient satisfaction has become a pivotal metric for assessing healthcare system effectiveness, reflecting the quality, accessibility, and responsiveness of healthcare services. This study aims to evaluate the role of patient satisfaction as an indicator of healthcare system performance using primary data collected from a diverse patient population. A cross-sectional survey was conducted, capturing quantitative and qualitative insights on factors such as access to care, quality of service, affordability, and patient outcomes. The findings revealed strong correlations between patient satisfaction and key healthcare performance metrics, including reduced wait times, effective communication, and perceived provider competence. Additionally, disparities in satisfaction levels were identified across demographic groups, highlighting systemic barriers such as affordability and accessibility in underserved populations. The study underscores the importance of integrating patient feedback into policy and operational decision-making to enhance patient-centered care and overall system effectiveness. Recommendations include adopting real-time satisfaction monitoring and addressing specific gaps to improve healthcare delivery and equity.